Cyberchondria among Filipino teacher education students - Reynold Padagas; Butch Stephen Duay; Jill Dalisay (Institute of Advanced Engineering and Science, 2022)
The internet-dense ecosystem has dramatically influenced the health-seeking behaviors of various population groups, including education students. Exposure to massive and readily accessible online health information increases health anxiety resulting in cyberchondria, a phenomenon characterized by excessive health search on the internet. This cross-sectional research study examined the level of cyberchondria among 179 teacher education students. The findings revealed that excessiveness, distress, reassurance, and compulsion subscales of cyberchondria were at moderate levels. However, higher correlations existed between excessiveness and compulsion subscales and between distress and compulsion subscales. Gender and programs enrolled have very weak relationships with cyberchondria subscales. The weakest association was between the programs enrolled by the students and all cyberchondria subscales. Meanwhile, students' age and year level have slightly higher but weak associations to the cyberchondria subscales, especially the excessiveness and distress subscales. As an intervention, an interdisciplinary collaboration between teacher education programs and the health-related institutes is recommended to promote awareness about cyberchondria, its prevention, and management.